Effect of Promotional Initiatives on Visits to a Dedicated Website for Physical Activity and Non-Communicable Disease in Luxembourg: An Event Study - Lion, Alexis; Thornton, Jane S.; Vaillant, Michel; Pertuy, Juliette; Besenius, Eric; Hardy, Cyrille; Delagardelle, Charles; Seil, Romain; Urhausen, Axel; Theisen, Daniel (Frontiers in Public Health, 2017)
The Sport-Santé project and its website (www.sport-sante.lu) promote physical activity for individuals with non-communicable diseases (NCDs) in Luxembourg. Our purpose was to perform an event study analysis to evaluate the effects of communication and promotional initiatives on the number of visits to the Sport-Santé website. Between September 2015 and May 2016, the Sport-Santé website was promoted during different initiatives, including participation in health-related events or publication of articles in local journals. The daily number of visits to www.sport-sante.lu website (i.e. our outcome) was recorded using Google Analytics and compared to a counterfactual collected with its benchmarking tool. The counterfactual was defined as the daily number of visits to websites in the same field. A model was created to evaluate the relationship between the number of visits to www.sport-sante.lu website and the number of visits to similar websites during a control period with no promotional initiatives (from July 2015 to September 2015). The effect of promotional initiatives was subsequently tested, by comparing the actual number of visits to our website (up to two days after each event) with the theoretical number of visits predicted by the model. Twenty-two initiatives were identified, of which 11 were participations at major health-related events and 11 publications of popular science articles. Of these 22 initiatives, the event study identified two popular science articles and one interactive workshop that significantly increased the daily number of visits to the www.sport-sante.lu website. One of the two articles was published on the day before the workshop was held, which did not allow us to distinguish its specific impact. The second article was published in the main national newspaper. This is the first time to our knowledge that an event study analysis has been used to evaluate the impact of promotional initiatives on the number of visits to a dedicated website for physical activity and NCDs. Our results indicate that some initiatives can aid in the number of visits, but in general their impact is limited. To observe an increased rate of participation in physical activity, additional promotional and evaluative strategies should be explored.